Large Abdominal Defect Closure: Case Series - Handini, Nurliati Sari; Tiza, Melina; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2016)
Background: We will report some experiences in managing challenging malignant cases on the abdominal wall, including a case of large, irradiated defect. All of those cases were consulted intraoperative immediately following tumor removal. The keystone random perforator flap was chosen among the option of solutions in large abdominal defect closure. This region has natural elasticity, which combines well with the multi-axial tissue recruitment of the flap Methods: Three cases of complicated abdominal defect were reconstructed using the keystone flaps supplied by non-identified (random) perforators. Results: All flaps survived without problem of vascularization, despite of its large defect, sequence of radiotherapy following reconstruction, infection, and with its margin unable to be freed from tumor. One out of three cases suffered from contaminated wound from stomal leakage, leading to dehiscence. Conclusion: The keystone flap is a useful and reliable random perforator-based flap, even in complex and challenging malignant cases of abdominal wall.